2012
DOI: 10.5455/bcp.20120403015900
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ferritin on Short-Term Treatment Response in Attention Deficit Hyperactivity Disorder

Abstract: Objectives Several studies have shown that iron deficiency and ferritin levels are associated with parent and teacher Attention Deficit Hyperactivity Disorder (ADHD) ratings. Although there are conflicting results, it has also been reported that iron supplementation may help to decrease ADHD symptoms. When all these previous studies are taken into account, it is clear that a large study investigating the effects of iron deficiency and ferritin levels on routine pharmacological treatment of ADHD with stimulants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Overall, the most common indicators of statistically significant positive associations in studies were SF (n = 21) [ 12 14 , 17 , 25 , 27 34 , 36 , 37 , 39 42 , 48 , 59 ], followed by Hb (n = 8) [ 12 , 13 , 17 , 30 , 33 , 40 , 51 , 59 ], SI (n = 6) [ 12 , 25 , 37 , 40 , 51 , 59 ], MCV (n = 5) [ 27 , 33 , 40 , 51 , 59 ], Hct (n = 2) [ 51 , 59 ], and total iron binding capacity (TIBC) (n = 2) [ 25 , 40 ]. Brain iron (BI) [ 39 ], mean corpuscular hemoglobina concentration (MCHC) [ 40 ], red cell distribution width (RDW) [ 34 ], sTfR/log ferritin index (SFI) [ 38 ], soluble transferrin receptor (sTfR) [ 38 ], and transferrin saturation (TSAT) [ 38 ], were indicators of a statistically significant positive association in 1 study each.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, the most common indicators of statistically significant positive associations in studies were SF (n = 21) [ 12 14 , 17 , 25 , 27 34 , 36 , 37 , 39 42 , 48 , 59 ], followed by Hb (n = 8) [ 12 , 13 , 17 , 30 , 33 , 40 , 51 , 59 ], SI (n = 6) [ 12 , 25 , 37 , 40 , 51 , 59 ], MCV (n = 5) [ 27 , 33 , 40 , 51 , 59 ], Hct (n = 2) [ 51 , 59 ], and total iron binding capacity (TIBC) (n = 2) [ 25 , 40 ]. Brain iron (BI) [ 39 ], mean corpuscular hemoglobina concentration (MCHC) [ 40 ], red cell distribution width (RDW) [ 34 ], sTfR/log ferritin index (SFI) [ 38 ], soluble transferrin receptor (sTfR) [ 38 ], and transferrin saturation (TSAT) [ 38 ], were indicators of a statistically significant positive association in 1 study each.…”
Section: Resultsmentioning
confidence: 99%
“…Only 11 association studies identified that fasting blood samples were taken for measuring iron parameters [ 16 , 28 , 29 , 31 , 33 , 35 , 36 , 40 , 42 , 45 , 51 ]. In the remainder, no information on timing of blood sampling was given.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, serum iron levels or transferrin [ 72 , 73 ] have been mentioned, although results are controversial. Nevertheless, most of the studies indicate lower serum ferritin levels in ADHD patients [ 32 , 33 , 69 , 70 , 71 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. Other reports found no significant relationship [ 89 , 95 , 96 , 97 , 98 , 99 , 100 ].…”
Section: Iron (Fe)mentioning
confidence: 99%